THE INFLUENCE OF COMPETENCE, INNOVATION AND ENTREPRENEURSHIP ORIENTATION IN IMPROVING PERFORMANCE OF MSMEs IN SERANG CITY - Nuraeni, Neni; M. Havidz Aima; Hernawati W Retno Wiratih (Dinasti International Journal of Digital Business Management, 2022)
This study aims to determine the effect of competence, innovation, and entrepreneurial orientation on the performance of MSMEs in the food sector in Serang City. This study uses quantitative methods with a sample size of 70 MSMEs. The sample was taken from the food sector MSME population in Serang City which had been running for at least 2 years. The sampling technique was non-probability sampling with purposive sampling method. The data analysis method used the Structural Equation Model (SEM) with the SmartPLS analysis tool. The results show that competence has a significant effect on MSMEs, innovation has a significant effect on MSMEs, and entrepreneurial orientation has a significant effect on MSME performance and competence, innovation, and entrepreneurial orientation simultaneously have a significant effect on MSME performance.